2016
DOI: 10.1016/j.cis.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multivalent cations and Tau on paclitaxel-stabilized microtubule assembly, disassembly, and structure

Abstract: In this review we describe recent studies directed at understanding the formation of novel nanoscale assemblies in biological materials systems. In particular, we focus on the effects of multivalent cations, and separately, of microtubule-associated protein (MAP) Tau, on microtubule (MT) ordering (bundling), MT disassembly, and MT structure. Counter-ion directed bundling of paclitaxel-stabilized MTs is a model electrostatic system, which parallels efforts to understand MT bundling by intrinsically disordered p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…61 Acylation of mPEG-NH 2 ( 1a,b ) with the lipid building block DOB (3,4-dioleyloxybenzoic acid) 48,49 yielded the control single-end-anchored PEG-lipids ( 3a,b ; L-PEG) on a gram scale. Monofunctionalization of amine-terminated PEG ( 2a,b ) with DOB to yield 5a,b requires a less reactive acylation reagent and low temperature 49,50 and yields the symmetric double-end-anchored PEG ( 4a,b ; L-PEG-L) as a side product. The monofunctionalized PEG ( 5a,b ) was separated by chromatography and acylated with oleic acid to yield the asymmetric double-end-anchored PEGs ( 6a,b ; L-PEG-L’).…”
Section: Resultsmentioning
confidence: 99%
“…61 Acylation of mPEG-NH 2 ( 1a,b ) with the lipid building block DOB (3,4-dioleyloxybenzoic acid) 48,49 yielded the control single-end-anchored PEG-lipids ( 3a,b ; L-PEG) on a gram scale. Monofunctionalization of amine-terminated PEG ( 2a,b ) with DOB to yield 5a,b requires a less reactive acylation reagent and low temperature 49,50 and yields the symmetric double-end-anchored PEG ( 4a,b ; L-PEG-L) as a side product. The monofunctionalized PEG ( 5a,b ) was separated by chromatography and acylated with oleic acid to yield the asymmetric double-end-anchored PEGs ( 6a,b ; L-PEG-L’).…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with previous studies, Tau is thought to stabilize axonal microtubules and Tau phosphorylation leads to microtubule depolymerization. 29 The motor dysfunction was observed in animal models and PD patients. 2 Here, behavioral tests were used to evaluate the motor function of the mice in each group including rotarod test, static rod test and pole test.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, divalent cation species appear to exhibit increasing effectiveness at promoting VIF aggregation according to their atomic number (14). Studies of other proteins have shown that ion-protein interactions can strongly depend on the ion species even when valency is unchanged (14,(16)(17)(18)(19)(20); this is often referred to as the Hofmeister effect. Corresponding species-specific interactions have not been widely explored in VIF networks.…”
Section: Introductionmentioning
confidence: 99%